MANAJEMEN PENGEMBANGAN KARIR DALAM MENINGKATKAN KINERJA KARYAWAN (STUDI PADA CV MOCCA MITRA AMANAH) - Najib, Muhammad Chairul; Khairul, Khairul; Efrianti, Kumara (Servqual: Jurnal Ilmu Manajemen, 2025)
In career development, management needs to examine the strategies and policies implemented and the extent to which these policies impact employee performance improvement. This study aims to explore how career programs: 1) positively influence employee performance enhancement, 2) provide employees with training opportunities and trust in their tasks, leading to improvements in various aspects of performance, including work productivity, quality, discipline, responsibility, and enthusiasm, and 3) directly contribute to improvements in both individual and team performance. The research method used is a qualitative approach with descriptive data analysis regarding career development, job satisfaction, and employee performance. The research was conducted at CV Mocca Mitra Amanah. Data collection techniques include interviews, observation, and documentation. The results show that CV Mocca Mitra Amanah implements various forms of career development through on-the-job training, job rotation, gradual promotion, and the assignment of additional responsibilities to high-performing employees. From a psychological perspective, career development increases employee motivation and loyalty. Many employees feel appreciated, more enthusiastic, and hopeful for continued growth. The level of trust given by management, both through training and additional task assignments, fosters greater responsibility and motivation among employees for future performance. In essence, there is a positive correlation between the company’s career development management and improvements in employee performance. The more structured and well-directed the career development implemented, the higher the level of performance exhibited by employees.